Mathematical finance and probability a discrete introduction - Medina Pablo Koch; Merino Sandro (Basel Birkhauser Verlag, 2003)
The objective of this book is to give a self-contained presentation to the theory underlying the valuation of derivative financial instruments, which is becoming a standard part of the toolbox of professionals in the financial industry. Not going for the
Keywords: Applied statistics; Financial mathematics; Probabilities